LIZINNI, Olga. Fluxus. Indagine sui fondamenti della metafisica e della física di Avicena. Bari: Edizioni di pagina, 2011, 679p. ISBN 978-88-7470-123-0. - Silva, Paula Oliveira e (Veritas (Porto Alegre), 2012)
.